Konservatif Cum Inklusif: Negosiasi Identitas Gereja Injili Kota Bengkulu di Tengah Pluralisme Agama - Kusmawanto, Dodi; Lattu, Izak Y.M. (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The main focus of this research is to describe the expression of identity negotiation that arises from the church's efforts to remain conservative in its doctrine and religious practices, and simultaneously interact with the cultural and religious diversity around it. This research uses qualitative methods with in-depth interview techniques and participant observation to collect data. The results of this research show that the Bengkulu City Evangelical Church congregation at the grassroots level adopts a conservative inclusion approach, where they are actively involved in dialogue and interaction with a pluralistic society and still maintain fundamental evangelical teachings. Negotiation of identity occurs through religious expression that recognizes and respects differences, but still maintains core beliefs and teachings. Factors such as local culture, social pressures, and internal church dynamics play an important role in the formation of this identity. This study provides a deeper understanding of how the Bengkulu City Evangelical Church group, especially at the grassroots, can maintain a conservative identity as Evangelicals in the context of inclusion, while responding to the dynamics of a pluralistic society. Such a religious attitude fulfills the principle of civic pluralism, namely acceptance without negating the authenticity of each individual's identity. The authenticity of the Evangelical Church group in Bengkulu City is manifested in its characteristics, namely conversion, activism, crucicentrism, and biblicism. Meanwhile, their acceptance of other religions is expressed and implemented through relationships and dialogues at structural, organizational, daily and symbolic levels. Fokus utama penelitian ini adalah menggambarkan ekspresi negosiasi identitas yang muncul dari upaya gereja untuk tetap konservatif dalam doktrin dan praktik keagamaannya, dan secara bersamaan berinteraksi dengan keragaman budaya dan agama di sekitarnya. Penelitian ini menggunakan metode kualitatif dengan teknik wawancara mendalam dan observasi partisipatif untuk mengumpulkan data. Hasil penelitian ini menunjukkan bahwa jemaat Gereja Injili Kota Bengkulu pada ranah akar rumput mengadopsi pendekatan inklusi yang konservatif. Mereka aktif terlibat dalam dialog dan interaksi dengan masyarakat yang plural serta tetap menjaga ajaran-ajaran fundamental Injili. Negosiasi identitas terjadi melalui ekspresi keagamaan yang mengakui dan menghormati perbedaan, namun tetap mempertahankan inti keyakinan dan pengajaran. Faktor-faktor seperti budaya lokal, tekanan sosial, dan dinamika internal gereja memainkan peran penting dalam pembentukan identitas ini. Studi ini memberikan pemahaman yang lebih dalam tentang bagaimana kelompok Gereja Injili Kota Bengkulu khususnya di akar rumput dapat menjaga identitas konservatif sebagai Injili dalam konteks inklusi, sembari merespons dinamika masyarakat pluralistik. Sikap beragama yang demikian memenuhi asas pluralisme kewargaan yaitu adanya penerimaan tanpa meniadakan keotentikan identitas masing-masing. Keotentikan kelompok Gereja Injili di Kota Bengkulu termanifestasi ke dalam karakteristiknya yaitu conversion, activism, crucicentrism, dan biblicism. Sedangkan penerimaan mereka terhadap agama-agama lain terekspresikan dan terimplementasikan melalui relasi dan dialog-dialog lingkup struktural, organisasional, sehari-hari, dan simbolik.